2013
DOI: 10.1590/s1982-56762013000600007
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Calonectria causing leaf blight and cutting rot of three forest tree species in Brazil

Abstract: Several species of Calonectria cause diseases on a wide range of forest tree species that are propagated either via seedlings or rooted cuttings. In nurseries these fungi cause damping-off, cutting and root rots, stem lesions, and leaf blights. Recently a Calonectria sp. was isolated from rooted cuttings of Anadenanthera peregrina (Fabaceae), Piptadenia gonoacantha (Fabaceae), and Azadirachta indica (Meliaceae) exhibiting leaf blight and cutting rot in a forest nursery at the Universidade Federal de Viçosa, Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…propagated commercially as non-natives in plantations. Results of this study have raised the number of species known from Brazil to 55 (Alfenas et al., 2013a, Alfenas et al., 2013b, Alfenas et al., 2015). Calonectria terricola , isolated from soil collected in a Eucalyptus plantation in Brazil, also formed part of the C. pteridis complex in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…propagated commercially as non-natives in plantations. Results of this study have raised the number of species known from Brazil to 55 (Alfenas et al., 2013a, Alfenas et al., 2013b, Alfenas et al., 2015). Calonectria terricola , isolated from soil collected in a Eucalyptus plantation in Brazil, also formed part of the C. pteridis complex in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Consensus sequences for each locus were assembled in MEGA v. 7 (Kumar et al. 2016) and compared with representative sequences from Alfenas et al., 2013a, Alfenas et al., 2013b, Alfenas et al., 2015, Chen et al., 2011 and Lombard et al., 2010a, Lombard et al., 2010b, Lombard et al., 2011, Lombard et al., 2015a. Subsequent alignments for each locus were generated in MAFFT v. 7.110 (Katoh & Standley 2013) and the ambiguously aligned regions of both ends were truncated.…”
Section: Methodsmentioning
confidence: 99%
“…Species of Calonectria are also rapidly dispersed via aerial dissemination and water movement, which leads to the transmission of Calonectria disease . Based on previous studies, at least 145 Calonectria species have been identified using molecular data and have been described worldwide (Crous 2002, Crous et al 2004, Lombard et al 2010a, b, c, 2011, 2016, Chen et al 2011, Alfenas et al 2013a, Gehesquière et al 2015. Sixty species were isolated from soil samples collected in subtropical or tropical regions (Crous 2002, Crous et al 2004, Lombard et al 2010a, b, c, 2015, 2016, Chen et al 2011, Alfenas et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…2004 ). Thus far however, the majority of the reports from Brazil focused on forestry crops, such as Pinus and Acacia ( Hodges and May, 1972 , Hodges et al., 1973 , Alfenas, 1986 , Dianese et al., 1986 , Novaes et al., 2012 , Alfenas et al., 2013a , Alfenas et al., 2013b ) and in particular on the epidemiology and disease control of Calonectria spp. associated with diseases of Eucalyptus in commercial plantations and nurseries ( Blum et al., 1992 , Mafia et al., 2008 , Mafia et al., 2009 , Graça et al., 2009 , Ferreira et al., 2012 , Alfenas et al., 2013c ).…”
Section: Introductionmentioning
confidence: 99%